Tinjauan Alur Prosedur Pelayanan Berdasarkan Jenis Pasien dan Penyelenggaraan Rekam Medis di Klinik X Kabupaten Sukoharjo - Wijaya, Chayanita Sekar; Azahra, Fatimah; Hidayati, Rahma Leyli; Syahrani, Vannia Shella Verahma (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2026)
The flow of procedures in patient care and medical record management is important for healthcare providers. If these two components are carried out properly, they can increase patient satisfaction with healthcare services. The purpose of this study is to review and provide a systematic overview of the flow of patient care procedures and medical record management at Clinic X in Sukoharjo Regency. This descriptive study was conducted at an outpatient clinic in Sukoharjo Regency. The objects of this study were the procedural flow of patient services and medical record management. The results of this study showed that the service system provided accommodated several types of patients, including general patients, BPJS patients, and partner patients from the clinic. The registration system is available in two models: online and offline BPJS registration. The Service Procedure Flow at Clinic X is already available and running well. Medical record management is already in place and is guided by Indonesian Minister of Health Regulation No. 24 of 2022. A suggestion for the future is that several services that still use manual medical records can be transferred to electronic medical records so that the services provided are more effective and efficient.